Study of dynamic characteristics of impact of two solid deformable bodies at impact speed of up to 100 m/s - D. I. Chernyavsky; D. D. Chernyavsky (Омский научный вестник)
The paper analyzes the dynamic dependencies between the impact force and the depth of the indenter penetration into the obstacle. The indenter is a hardened steel ball. The target is made in the form of a rod from various types of steel, duralumin, aluminum and lead. As a result of digitizing the graphs of dependencies, interpolation formulas are obtained for different phases of the impact (the first phase of the impact is compression; the second phase of the impact is unloading). In the course of the analysis of interpolation formulas, absolute and relative data on the transformation of the initial kinetic energy of the indenter into the distribution of energies after impact are obtained: the value of the kinetic energy of the indenter after the impact, the values of the energy of elastic and plastic deformations, and the energy of shock waves. The results obtained can be used to design impact machines with an indenter impact speed against an obstacle up to 100 m/s.